Exploring the use of solid fuels for cooking and household air pollution in informal settlements through photovoice: The Fuel to Pot study in Ndirande (Malawi) and Mukuru (Kenya). - Isabelle Uny; Tracy Chasima; Line Caes; Lusizi Kambalame; Moses V M Chamba; Limbani Kalumbi; Fred Orina; Heather Price; Sian Lucas; Maria Nyikuri; Sean Semple; Hellen Meme (PLoS ONE)
Introduction Worldwide, 2.4 billion people rely on solid fuels such as wood or charcoal for cooking, leading to approximately 3.2 million deaths per year from illnesses attributable to household air pollution. Across Africa, household air pollution generated by solid fuel use accounts for nearly 700,000 deaths each year. Most studies to date have focused either household air pollution exposure, its impacts on particular health outcomes or on the efficacy of mitigation interventions. However, the economic, social, and cultural determinants of household air pollution in Africa are still poorly understood. The purpose of this study was to explore people's experience of using solid fuels for cooking in two informal settlements, Ndirande in Malawi and Mukuru in Kenya, and the associated harms caused by household air pollution. Methods We adopted a community-based participatory method, photovoice, which was conducted with 9 participants in Ndirande and 10 participants in Mukuru. Participants took pictures reflecting their experiences and perceptions of household air pollution harms over a two-week period, and later discussed, sorted and analysed those in a series of meetings. Thematic analysis was used to analyse the data. Results With their pictures, participants described fuel stacking and switching behaviours in their communities. They described a mix of charcoal, firewood and other biomass fuels use. They also expressed their awareness and perceptions of the harms caused by smoke when cooking. Participants explained the simple behaviours used by residents to minimize the harms of household air pollution to themselves and within their own household. Other themes explored the roles and responsibilities for procuring fuels in the home, and the stated solutions required to address the issues and manage the transition to cleaner fuels in those informal settlements. Conclusion This study highlights not only the need to understand the daily life, priorities and concerns of those who use solid fuels on informal settlements, but also the urgency to place them and their experience at the heart of the solutions that will reduce the health harms of household air pollution.